Integrating parametric modeling with BIM through generative programming for the production of NURBS surfaces and structures - Silva, Lilian Maciel Furtado (2019)
A workflow for integration of parametric modeling with BIM, using generative-programming, is described and tested in this research. The objective is to take advantage of these two distinctive design paradigms. This paper describes a design experiment that required a NURBS roof generated by sweeping profiles along a curved path. We assumed the use of multiple applications, using various file formats, are facts and are unlikely to disappear. Given that interoperability issues will certainly arise, we propose and test a design workflow using parametric modeling, generative programming, and building information modeling. Our major contribution was defining a workflow for designing NURBS surfaces and corresponding supporting structures enhancing interoperability among different applications through generative-programming.